2000
DOI: 10.1182/blood.v96.9.3094.h8003094_3094_3101
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of circulating HIV-specific CD8+ T cells in chronic human immunodeficiency virus infection

Abstract: The functional status of circulating human immunodeficiency (HIV)-specific CD8 T cells in chronically infected subjects was evaluated. By flow cytometry, only 5 of 7 subjects had detectable CD8 T cells that produced IFN-γ after stimulation with HIV-infected primary CD4 T cells. In 2 subjects, the frequency of IFN-γ–producing cells increased 4-fold when IL-2 was added to the culture medium; in another subject, IFN-γ–producing cells could be detected only after IL-2 was added. IFN-γ–producing cells ranged from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 57 publications
6
68
1
2
Order By: Relevance
“…In case of chronic virus infections, cancers (194) and persistent bacterial infections (195), continued in vivo exposure to high levels of antigen leads to severe dysfunction of CD8 T cells, also designated CD8 T cell exhaustion. Originally CD8 T cell exhaustion was described after chronic infection of mice with LCMV (196), but was also shown to occur after HCV (197) and HIV (198–202) infection of humans, SIV in rhesus macaques (203), polyomavirus (204), adenovirus (205), Friend retrovirus (206) and mouse hepatitis virus (207) infection of mice.…”
Section: ‘Memory’ During Chronic Productive Infectionmentioning
confidence: 99%
“…In case of chronic virus infections, cancers (194) and persistent bacterial infections (195), continued in vivo exposure to high levels of antigen leads to severe dysfunction of CD8 T cells, also designated CD8 T cell exhaustion. Originally CD8 T cell exhaustion was described after chronic infection of mice with LCMV (196), but was also shown to occur after HCV (197) and HIV (198–202) infection of humans, SIV in rhesus macaques (203), polyomavirus (204), adenovirus (205), Friend retrovirus (206) and mouse hepatitis virus (207) infection of mice.…”
Section: ‘Memory’ During Chronic Productive Infectionmentioning
confidence: 99%
“…Attenuation of viral‐specific T‐cell responses in chronic viral infections has been related to a phenomenon known as T‐cell exhaustion 10, 11. In recent years, T‐cell exhaustion in persistent viral infections has been emphasized to be modulated through the “programmed death‐1” (PD‐1) signaling pathway 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive transfer experiments revealed that a large fraction of specific CTL disappeared from the circulation and from the lymphoid organs. This process has also been documented for chronic viral infections, and is referred to as exhaustion 19, 21–26. The phenotype of CTL that resist physical deletion in the presence of a chronic infection has been analyzed before.…”
Section: Discussionmentioning
confidence: 99%